Exploration of genetic characterization in hyperprogressive disease after immunotherapy retreatment in a patient with LCNEC: A case report - Yao Zhang; Jiayao Yang; Tianyu Shao; Jialu Chen; Qijin Shu; Liumei Shou (Human Vaccines & Immunotherapeutics)
Immune checkpoint inhibitors (ICIs) have emerged as a promising therapeutic option for large cell neuroendocrine carcinoma (LCNEC). However, various studies have suggested a potential risk of hyperprogressive disease (HPD) in patients receiving ICI, which might be associated with gene alterations. Here, this is the first report on an unknown primary LCNEC patient who had achieved a long-term response from ICI treatment (atezolizumab), but developed HPD after tumor progression due to receiving another ICI agent (serplulimab). The mutation region of FAT4, SMARCA4, CYLD, CTNNB1, and KIT was altered prior to serplulimab treatment compared to before atezolizumab treatment. This case suggested a potential association between these mutated genes and HPD. Patients with the aforementioned genes should caution when selecting ICI treatment. These findings required further confirmation in a larger study cohort.